The darkness-within-the-light of contemporary fiction: Agamben's missing reader and Ben Lerner's 10:04. Issue 10 (2nd October 2020) - Davies, Ben
ABSTRACT: The role of reading and the reader in Giorgio Agamben's 'What is the Contemporary?' is ambiguous. Rather than examining the importance of reading he emphasises, Agamben explores what it means to be contemporary. Reading Ben Lerner's 10:04 in the light (and darkness) of Agamben's essay, I argue both that the essay can be read as a theory of 'contemporary reading' and that 10:04 reflects its own contemporariness. 10:04 creates forms of contemporary relationality through a poetics of light and darkness, and positions its reader within a caesural space, in which she is proximate to, and distanced from, the text. This reading therefore opens up an understanding of the contemporary reader that is relational, not historical. Correlatively, 10:04 also raises problematics of the study of the contemporary novel more widely. I shall read a moment of deletion, for instance, to argue that analysis of the contemporary novel must include the field's un-written materials. I shall likewise analyse 10:04 's interest in the reader to argue that non-readers also form part of the field and deserve critical attention. Ultimately, 10:04 unveils the darkness-within-the-light of the contemporary novel and reader, both of which are missing from Agamben's essay.